Progress in Traditional Chinese Medicine Against Respiratory Viruses: A Review - Li, Bao-Hong; Li, Zhong-Yuan; Liu, Miao-Miao; Tian, Jing-Zhen; Cui, Qing-Hua (Frontiers in Pharmacology, 2021)
Respiratory viruses, such as severe acute respiratory syndrome coronavirus (SARS-CoV)-1, SARS-CoV-2, influenza A viruses, and respiratory syncytial virus, pose a serious threat to society. Based on the guiding principles of “holism” and “syndrome differentiation and treatment”, traditional Chinese medicine (TCM) has unique advantages in the treatment of respiratory virus diseases owing to the synergistic effect of multiple components and targets, which prevents drug resistance from arising. According to TCM theory, there are two main strategies in antiviral treatments, namely “dispelling evil” and “fu zheng”. Dispelling evil corresponds to the direct inhibition of virus growth and fu zheng corresponds to immune regulation, inflammation control, and tissue protection in the host. In this review, current progress in using TCMs against respiratory viruses is summarized according to modern biological theories. The prospects for developing TCMs against respiratory viruses is discussed to provide a reference for the research and development of innovative TCMs with multiple components, multiple targets, and low toxicity.